Expresión de elF3f en Schizosaccharomyces pombe - Hernández Soto, Paulina (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
Schizosaccharomyces pombe (S. pombe) or fission yeast is a unicellular eukaryotic free-living bacilli as approximately 2 to 3 microns in diameter and from 7 to 14 long. This yeast was isolated from African beer over a hundred years ago, hence the name pombe which means "from beer" in Swahili. www-rcf.usc.edu/~forsburg/main.html S. pombe has been a model organism to study eucariónticas cells, especially in cell cycle studies. In 2001 the Nobel prize was awarded to Leland Hartwell and Paul Nurse for the discovery of key regulators of the cell cycle, ie, the mechanism that controls cell division in S. pombe (Gupta, 2001). S. pombe mitotic cycle completes in about 150 minutes under optimal growing conditions and is relatively easy to genetically modify, without which is a haploid organism. S. pombe genome is fully sequenced and consists of 13.8 million base pairs on three chromosomes which have been identified 4.824 genes encoding proteins, this being the date the smallest number of genes in a eukaryotic genome content. S. pombe genome characterized 43% of their genes have introns small, many more introns of those found in Saccharomyces cerevisiae (S. cerevisiae) as only 5% of their genes contain introns. Besides the differences between the genomes of S. cerevisiae and S. pombe, we found differences in the way division: the first is divided asymmetrically by budding and the second by symmetrical division, the latter being similar to the division in higher eukaryotes. Because of this characteristic, S. pombe is known as fission yeas.

Schizosaccharomyces pombe (S. pombe) o levadura de fisión es un eucarionte unicelular de vida libre, en forma de bacilo de aproximadamente 2 a 3 micras de diámetro y de 7 a 14 de longitud. Esta levadura fue aislada de cerveza Africana hace más de cien años, de ahí el nombre de pombe que significa “proveniente de la cerveza” en Swahili. www-rcf.usc.edu/~forsburg/main.html S. pombe ha sido un organismo modelo en el estudio de células eucarióticas, especialmente en estudios de ciclo celular. En el 2001 se entregó el premio Nobel a Paul Nurse y Leland Hartwell por el descubrimiento de los reguladores clave del ciclo celular, es decir, del mecanismo que controla la división celular en S. pombe (Gupta, 2001). S. pombe completa su ciclo mitótico en aproximadamente 150 minutos en condiciones óptimas de cultivo y es relativamente fácil modificarla genéticamente, sin contar que es un organismo haploide. El genoma de S. pombe se encuentra totalmente secuenciado y consta de 13.8 millones de pares de bases distribuidos en tres cromosomas donde se han identificado 4,824 genes que codifican proteínas, siendo éste a la fecha el número más pequeño de genes contenido en un genoma eucarionte. El genoma de S. pombe se caracteriza porque el 43% de sus genes tienen intrones de tamaño pequeño, muchos más intrones de los que podemos encontrar en Saccharomyces cerevisiae (S. cerevisiae) ya que solo el 5% de sus genes contiene intrones. Además de las diferencias entre los genomas de S. cerevisiae y S. pombe, encontramos diferencias en su forma de división: la primera se divide de manera asimétrica por gemación y la segunda por división simétrica, siendo ésta última semejante a la división en eucariontes superiores. Debido a esta característica, a S. pombe se le conoce como la levadura de fisión (Wood et al., 2002).
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2008-0010; Levadura; Eucarionte; Ciclo celular; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3846